2007
DOI: 10.4141/cjps07160
|View full text |Cite
|
Sign up to set email alerts
|

Organic production of vegetables: State of the art and challenges

Abstract: Dorais, M. 2007. Organic production of vegetables: State of the art and challenges. Can. J. Plant Sci. 87: 1055-1066. In light of the growing concern of Canadians about animal waste, environmental pollution from fertilizers, water quality and greenhouse gas effects, as well as their growing interest in organically grown foods (20% annual growth in North America), the development of sustainable organic production systems for vegetable crops is essential for consumer satisfaction and Canadian grower competitiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 101 publications
3
39
0
1
Order By: Relevance
“…Considering the relatively low amount (Table 2) of products blended with the substrate (in the substrate treatments), and/or delivered through the fertigation system (in the fertigation treatments), the increase in most of the measured plant parameters (Table 3, Table 4 and Table 5) was remarkable. In fact, the total quantity of products used was in the order of 5-15% of the minimum dose for common organic fertilizers and/or generic amendments, which are normally applied in agriculture (Dorais, 2007). In recent on-field red pepper and tomato cultivation trials, Sortino et al, 2013 andSortino et al, 2014 found that the application of 700 kg ha −1 of urban biowastes' hydrolysates did not alter significantly the soil chemical composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the relatively low amount (Table 2) of products blended with the substrate (in the substrate treatments), and/or delivered through the fertigation system (in the fertigation treatments), the increase in most of the measured plant parameters (Table 3, Table 4 and Table 5) was remarkable. In fact, the total quantity of products used was in the order of 5-15% of the minimum dose for common organic fertilizers and/or generic amendments, which are normally applied in agriculture (Dorais, 2007). In recent on-field red pepper and tomato cultivation trials, Sortino et al, 2013 andSortino et al, 2014 found that the application of 700 kg ha −1 of urban biowastes' hydrolysates did not alter significantly the soil chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane retentate containing the soluble hydrolysate, and the solid insoluble hydrolysate were dried in ventilated oven at 60 °C. The final dried products were analyzed according to previously reported methods and yielded the analytical values reported in TableTable 1 Treatments were arranged based on the following criteria and/or objectives: (i) to supply amounts of treatments' products per unit area or plant, which were negligible, compared with the applied doses of most biowaste sourced materials (such as compost), which are reported in literature (Dorais, 2007); (ii) to supply amounts of macronutrients contributed by the treatments' products, which were negligible, compared with the normally applied amounts of chemical fertilizers; (iii) to account for effects of treatments' products as a function of their formulation and distribution mode; (iv) to study possible interactions between products obtained by different sourcing materials. Two different types (factors of variability) of treatments were applied (Table 2): (i) the substrate treatments (SUB) comprising 11 treatments and the control, and the fertigation (FERT) treatments comprising 2 treatments and the control.…”
Section: Biobased Materials Under Investigationmentioning
confidence: 99%
“…The second would be to use biodegradable cord from vegetable fibres (Angelini et al, 2000), which can be obtained near the greenhouse areas, to reduce the cost with respect to the price of plastic cords. In addition, if the biodegradable cords are accompanied by the practice of a more ecological type of agriculture (Dorais, 2007) with lower rates of agrochemical application, the vegetable remains would be easier to treat chemically and the final briquettes made for combustion could compete environmentally with the composting suggested by Anton et al (2005), the briquettes being a reusable product, as indicated by Munoz and Riley (2008). Finally, as observed by Gomes et al (1997), the decrease in fossil fuels is encouraging research on alternative energy sources, with agricultural products playing a major role, although, if their fundamental characteristic that defines a fuel as such is its high heating value, the results indicate that the briquettes from the greenhouse plant remains could be considered as a more or less average fuel.…”
Section: Discussionmentioning
confidence: 99%
“…Anton et al (2005) demonstrated from the environmental standpoint that with greenhouse wastes the best approach, rather than incineration, is to classify them, recycle them, and reuse them, advising that plant remains be composted. Similarly, Dorais (2007) observed the need to develop sustainable development by ecological production systems of vegetables, which would increase consumer satisfaction at the same time as improving competitiveness of the producers. Also, Munoz and Riley (2008) have indicated that the reuse of agricultural wastes is becoming more widespread due to the environmental impact of generated waste.…”
Section: Introductionmentioning
confidence: 99%
“…The added soil cover (50-90% cover) provided by GMrs mulches following rolling compared with tillage ( < 5% cover) can provide important soil and water conservation benefits, although the impact of potentially reduced soil temperatures and spring available N needs further examination. No-till systems for organic vegetable production are also being increasingly explored such as no-till or rolled hairy vetch and fall rye cover crop systems for field tomatoes, cucumber, zucchini and bell pepper production in the USA and Canada [64][65][66][67].…”
Section: Soil Organic Matter Storagementioning
confidence: 99%